A Male victims of intimate partner violence: a systematic review. - Gonzales Ruiz, Erika Yobana (2023)
The main objective of this investigation was to carry out a systematic review of the factors associated with male victims of intimate partner violence; the specific objectives were to identify the different forms of intimidation and to determine the type of violence most frequently perpetrated against men, as well as to identify the different reasons for refusing to seek help. The sample consisted of 45 articles, which were found in different databases such as Researchgate, Redalyc, PubMed Central, SAGE Journals, ProQuest, Dialnet, EBSCO, Scielo, ScienceDirect, REDIB, Medigraphic and InfoMED. These articles were categorized by authors, year, title, factors, types, modalities, barriers, relationship with the victim, instrument, country, language, sample and conclusions. The main results of the individual factors were partner abuse, low self-esteem and emotional dependence; family factors included domestic violence, low income and coming from a dysfunctional home; and cultural factors included gender roles, invisibilization of violence and stereotypes. In addition, psychological violence was identified as the most predominant type of abuse against men.